IMPACTS OF INTERNAL PARTY DEMOCRACY ON PERFORMANCE OF ALL PROGRESSIVE CONGRESS IN THE 2023 GENERAL ELECTIONS IN NIGERIA - IBRAHIM NUAIMU DANBALA; CELESTINE OGECHUKWU OKAFOR (International Studies Journal)
This study examined the impacts of internal party democracy on performance of All Progressive Congress (APC) in the 2023 general elections in Nigeria. The issue of advancing internal democracy especially as it concerns the selection of candidate within political parties in Nigeria has been a contentious topic. Promoting internal democracy in political parties has not only gained ground in modern day politics and governance but it is believed that such practices will encourage democratic culture generally. Thus, it is argued that political parties across the globe have adopted party primaries as a mechanism for selecting candidates for elections. The study adopted documentary method for data collection while relying on sequential qualitative analytic techniques. The study also utilized the group theory as it theoretical framework for analysis. This paper argues that it is becoming worrisome that All Progressive Congress find it difficult to conduct free and fair primary elections and this has continued to increase internal party crisis and threatens the very survival of political party system and the relevance of practicing democracy in Nigeria. Findings reveal that the adoption of different modes of primary election by APC for selection of candidates in different states in Nigeria appears to be an attempt to subvert the will of the people. The study concluded that it is uncommon for political parties to experience internal conflicts and disagreements, especially when there are diverse group interests and agenda among party members. The paper therefore, recommends among others that individuals should join political party based on shared ideology rather than personal ambition.